Ecology and management issues of Mikania micrantha in Chitwan Naitonal Park, Nepal - Sapkota, Loknath (Banko Janakari, 2009)
Mikania micrantha, one of the worst invasive weeds in the world, is a plant of Neotropical origin and threatening to the ecosystem of most countries within the moist tropical zones of south east Asia. Three habitat types were taken to study the ecology and management issues of the weed. The study was conducted from October, 2006 to February, 2007 taking random sampling intensity of 0.3%, 0.03% and 0.0012% of the invaded area for tree, shrub and herb, respectively and plot size were 20*25m, 5*5m and 1*1m, accordingly. The riparian, edge, grassland with sparse tree and shrub, low canopy area of natural and afforested forest were found to be highly invaded by the weed. A total of 102 plant species were affected in various degrees by the weed. The highest invasion was found in Dalbegia sissoo tree in afforested land and the prevalent effect was observed in Bombax ceiba of below 17 cm DBH. Most of the trees of above 30 cm DBH were found to be low invasion. All the shrub species in invaded area were highly smothered and only some herbs like Ageratum conizoides, Aquisetum debile, Eragrostis unioloides, Diplazium esculentum and Tectoria macrodonta were observed to be exposed. Co-evolved rust pathogen, Puccinia spegazzini has been reported to be able to control the weed. Managing grassland, the intensive and extensive production of NTFP in community forest, cutting of nutrients and moisture for climber and mulching on creeper of Mikania and introduction of parasite plant like Cuscuta reflexa have shown as appropriate measure to keep up the weed in acceptable level. Keywords: Invasive, Puccinia spegazzini, Mulching, Control, Threatening, Smothered. doi: 10.3126/banko.v17i2.2153 Banko Janakari, Vol. 17, No. 2, 27-39